Generalized Fractional Integral Operators Introduced by Saigohaving the Gauss Hypergeometric Function as Kernel: Applications and Properties of Saigo Operators (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Because of the general nature of the multivariable H-function and Saigo operators, a large number of new and referred to results can be inferred as specific instances of the fundamental results. In this way, first we acquire the image of the r-product of various H-functions in the Saigo operators. This image is likewise very broad in nature and is of intrigue and significance independent from anyone else. Next, we get the image of r-product of Bessel function of the principal kind in Saigo operators.